2014
DOI: 10.1021/jp504176b
|View full text |Cite
|
Sign up to set email alerts
|

Unique Identification of Single-Walled Carbon Nanotubes in Electrospun Fibers

Abstract: Single-walled carbon nanotubes (SWNTs) have been exfoliated in a poly(vinyl alcohol) (PVA) matrix using electrospinning. Raman features of SWNTs with single chirality were studied systematically in terms of the band frequency, intensity, and full width at half-maximum (fwhm). Polarized Raman spectroscopy was used to investigate the orientation of SWNTs, and it was found they were highly aligned along the fiber axis. The response of the nanotube G′-band to external strain for SWNT has been found to be dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This has been true for both PS/ CNC and PVA/CNC fibres regardless of the differences in electrospinning conditions and fibre diameters. Previous work has shown that single-walled carbon nanotubes (SWNTs) can be oriented in electrospun PVA fibres [23][24][25]. Given that the lateral sizes of CNCs and SWNTS are similar, it is surprising that orientation is not achieved with the present system.…”
Section: Raman Spectroscopic Characterization Of Cnc Orientationmentioning
confidence: 76%
“…This has been true for both PS/ CNC and PVA/CNC fibres regardless of the differences in electrospinning conditions and fibre diameters. Previous work has shown that single-walled carbon nanotubes (SWNTs) can be oriented in electrospun PVA fibres [23][24][25]. Given that the lateral sizes of CNCs and SWNTS are similar, it is surprising that orientation is not achieved with the present system.…”
Section: Raman Spectroscopic Characterization Of Cnc Orientationmentioning
confidence: 76%
“…When the angle between the polarization direction of the laser and the axis of CNT changes, the intensity of the polarized Raman spectrum for CNTs that have a certain degree of orientation will be varied; 28,29 however, that for CNTs with random distribution almost does not change. 30 Figure 5 gives polarized Raman spectra of m-CNT0.3/EP and t-CNT0.3/EP composites, in which 0°, 30°, 60°, and 90°are polarization angles. The Gband 31 of CNTs appears at 1610 cm −1 in each spectrum, however, the intensity of the G-band is increased and then decreased as the polarization angle increases in the spectra of m-CNT0.3/EP composites.…”
Section: Resultsmentioning
confidence: 99%
“…Polarized Raman spectra can be used to characterize the orientation of CNTs in composites. When the angle between the polarization direction of the laser and the axis of CNT changes, the intensity of the polarized Raman spectrum for CNTs that have a certain degree of orientation will be varied; , however, that for CNTs with random distribution almost does not change Figure gives polarized Raman spectra of m-CNT0.3/EP and t-CNT0.3/EP composites, in which 0°, 30°, 60°, and 90° are polarization angles.…”
Section: Results and Discussionmentioning
confidence: 99%